Concentration-dependent SILAR synthesized Di-bismuth copper oxide nano-materials electrode in asymmetric supercapacitor - Bobade, R. G.; Dabke, N. B.; Shaikh, Shoyebmohamad F.; Al-Enizi, Abdullah M.; Pandit, Bidhan; Lokhande, B. J.; Ambare, R. C. (Journal of Materials Science-Materials in Electronics, 2024)
In this study, we present a novel approach to prepare bismuth oxide deposited on copper substrate (Bi2CuO4) electrodes using a binder-free successive ionic layer adsorption and reaction (SILAR) technique, demonstrating their potential for energy storage applications. The resulting Bi2CuO4 electrode exhibits a tetragonal crystal structure with a polycrystalline nature, as confirmed by X-ray diffraction (XRD). Field emission scanning electron microscopy (FE-SEM) reveals a distinctive sphere-like structure with hydrophilic characteristics, as determined from contact angle measurements. X-ray photoelectron spectroscopy (XPS) further validates the composition of the sample. The electrochemical performance of Bi2CuO4 is remarkable, with a specific capacitance (SC) of 1795.9 F/g at 16 mA/cm(2). When used as an anode in an asymmetric solid-state device (ASSD) alongside activated carbon (AC) as the cathode, the Bi2CuO4 electrode attains a maximum energy density (SE) of 169.5 Wh/kg at 16 mA/cm(2) and a peak power density (SP) of 15.9 kW/kg at 24 mA/cm(2). In a 1 M KOH-polyvinyl alcohol (PVA) polymer solution, the Bi2CuO4//AC pencil-type cell achieves a superior SC of 94.5 F/g at 5 mV/s, retaining approximately 92% of its initial performance even after 5000 charge-discharge cycles. The resulting SE and SP are 43.1 Wh/kg and 5.2 kW/kg at 10 mA/cm(2), respectively. This research presents an efficient and straightforward synthesis method for producing high-performance pencil-type supercapacitors at a laboratory scale. Furthermore, we demonstrate the potential of a homemade pencil-type supercapacitor device (Bi2CuO4//AC) to power a light-emitting diode (LED), highlighting its practical utility in various energy storage applications.

Influence of deposition potential on electrodeposited bismuth-copper oxide electrodes for asymmetric supercapacitor - Bobade, Rushikesh G.; Dabke, Niteen B.; Shaikh, Shoyebmohamad F.; Al-Enizi, Abdullah M.; Pandit, Bidhan; Lokhande, Balkrishna J.; Ambare, Revanappa C. (BATTERIES & SUPERCAPS, 2024)
Keywords: Bi2CuO4; Deposition Potential; Electrodeposition; supercapacitor; thin film